System information modelling in practice: Analysis of tender documentation quality in a mining mega-project - Love, Peter; Zhou, Jingyang; Matthews, Jane; Sing, M.; Edwards, D. (Elsevier BV, 2017)
© 2017 Elsevier B.V. The quality of information contained in tender documentation produced using Computer-Aided-Design (CAD) and provided in a hard-copy format to an electrical engineering contractor for a port expansion facility, which formed an integral part of an Iron Ore mega-project is analyzed. A System Information Model (SIM), which is an object oriented approach, was retrospectively constructed from the documentation provided to assist the contractor with their tender bid preparation. During the creation of the SIM, a total of 426 errors and omissions were found to be contained within the 77 tender ‘drawing’ documents supplied to the contractor by an Engineering, Construction, Procurement and Management (EPCM). Surprisingly, 70 drawings referenced in the tender documentation, and the Input/Output lists and Cause/Effect drawings were not provided. Yet, the electrical contractor was required by the EPCM organization to provide a lump sum bid and also guarantee the proposed schedule would be met; the financial risks were too high and as a result the contractor decided not to submit a bid. It is suggested that if the original tender documentation had been prepared using a SIM rather than CAD, the quality of information presented to the contractor would have enabled them to submit a competitive bid for the works. The research concludes that the economic performance and productivity of mining projects can be significantly improved by using a SIM to engineer and document electrical instrumentation and control (EIC) systems.